Gender equality, disability, and social inclusion in the Philippines: Progress, challenges, and opportunities in SDG 5 and SDG 10 - Albert, Jose Ramon G.; Bayudan-Dacuycuy, Connie; Quisumbing, Agnes R.; Basillote, Lovelaine; Cabalfin, Deanne Lorraine; Vargas, Anna Rita; Luzon, Paola Ellaine; Mahmoud, Mohammad (Philippine Institute for Development Studies, 2025)
This study examines the Philippines' progress toward achieving gender equality, disability inclusion, and social inclusion (GEDSI) through an analysis of available data on Goals 5 (Gender Equality) and 10 (Reduced Inequalities) of the Sustainable Development Goals (SDGs) from 2015 to 2025. The research reveals substantial policy achievements alongside critical implementation gaps that undermine transformational potential, with intersecting forms of marginalization creating complex patterns of exclusion that require integrated policy responses.